2020
DOI: 10.1186/s13071-020-04374-x
|View full text |Cite
|
Sign up to set email alerts
|

Larval ecology and infestation indices of two major arbovirus vectors, Aedes aegypti and Aedes albopictus (Diptera: Culicidae), in Brazzaville, the capital city of the Republic of the Congo

Abstract: Background Invasive mosquito species, such as Aedes albopictus in Congo can affect the distribution of native species, changing the vector composition and pattern of disease transmission. Here, we comparatively establish the geographical distribution and larval habitat preference of Ae. aegypti and Ae. albopictus and the risk of arbovirus disease outbreaks using Stegomyia indices in the city of Brazzaville, the capital of the Republic of the Congo. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
34
0
6

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 25 publications
(46 citation statements)
references
References 59 publications
6
34
0
6
Order By: Relevance
“…albopictus was highly prevalent in discarded tires, empty cans and containers. These findings were in accordance with previous studies in Cameroon [ 41 , 42 ] and elsewhere in central Africa [ 43 , 44 , 45 ]. Used vehicle tires have been reported as the main larval habitats and presumably one of the most productive for Ae.…”
Section: Discussionsupporting
confidence: 94%
“…albopictus was highly prevalent in discarded tires, empty cans and containers. These findings were in accordance with previous studies in Cameroon [ 41 , 42 ] and elsewhere in central Africa [ 43 , 44 , 45 ]. Used vehicle tires have been reported as the main larval habitats and presumably one of the most productive for Ae.…”
Section: Discussionsupporting
confidence: 94%
“…Our current findings are consistent with those of a previous study conducted in 2016 in KPP, Thailand, which found a small number of discarded coconut shells around houses and most of them were infested with Aedes larvae [26]. This observation is also in agreement with previous studies in other regions of the Central African Republic and the Republic of the Congo, where the lack of pipe water promotes the storage of water in households and there is a lack of waste management [27,28]. Tires, which were the discarded containers that were most commonly infested with larvae, are one of the most important sources of adult vector populations, since they generated 59.6% of the Aedes larval presence in our study.…”
Section: Discussionsupporting
confidence: 93%
“…albopictus adults were trapped inside houses, which is consistent with an earlier study that demonstrated larvae of both species coexisting in the same natural containers (coconut shells, husks, and bracts) [30]. Colonization of both vector species was reported to be especially high in trash and discarded containers [27,28,31]. Sharing the same vectors as other arboviruses, e.g., Zika and Chikungunya viruses, may explain this.…”
Section: Discussionsupporting
confidence: 87%
“…Blue-Green Space Urban Space [12,19,23] Parks and cemeteries Suburban neighborhood [24] Highly vegetated suburban neighborhoods Scarcely vegetated urban neighborhoods [25] Farm and park Urban and suburban neighborhoods [22,25] Parks Urban and suburban neighborhoods [26][27][28] Vegetated suburban areas Scarcely vegetated urban areas [29] Urban forest Peri-urban neighborhood [30] Urban green space Densely urban area Unrelated results were eliminated during the screening process. The abundance, mean, and standard deviation for individual mosquito species were extracted from the studies and categorized by treatment.…”
Section: Studymentioning
confidence: 99%